Organizational Coordination and Performance in Hospital Accounting Information Systems: An Empirical Investigation - Kim, K. Kyu (The Accounting Review, 1988)
[This paper describes a field study of 28 hospital accounting information systems (HAIS) development groups designed to address the issue of "fit" between organizational context and the effective design of management accounting systems (MAS). Hypotheses are developed for studying the interaction effects of contextual and MAS design variables on performance. The findings indicate that the match between HAIS task predictability and coordination modes is significantly associated with good performance as measured by user information satisfaction.]